The Holocaust as a Source for Jewish-Christian Bonding - Greenberg, Gershon (Studies in Christian-Jewish relations, 2009)
The crucible of the Holocaust distilled Judaism to its essence. The conception of sacred death which emerged included the elements of Akedah, physical suffering, love between God and man, and crucifixion. These elements were identified with sacred death by the Church Fathers during Christianity's formative martyrdom-period. But they were already present in Judaism and continued to be so into the modern era. The sacred death of the Holocaust is a source for intimate bonding between Judaism and Christianity, as proposed by Marcel Dubois, Franklin Sherman and Clemens Thoma. Nor does the bonding deplete the respective identities (for Judaism, the national suffering which redeemed the world, for Christianity the mystery of Christ's crucifixion which transfigured suffering and death into a crucible of resurrection) - as Juergen Moltman implies (according to Gregory Baum). The bonding also sets aside grounds for conversion to Christianity.